Fostering environmental personal norms: the role of environmental education in Nigerian pre-service teachers’ environmental knowledge, pro-environmental beliefs and behaviours - Obiagu, Adaobiagu; Ocheje, John; Ofodum, Ifunanya; Eze, Emmanuel (Environmental education research, 2024)
This research investigated the role of environmental education (EE) in acquiring environmental knowledge, pro-environmental beliefs and pro-environmental behaviours among a sample of pre-service teachers who undertook an EE course (n = 177) and those who did not undertake an EE course (n = 203) in a Nigerian university. Results showed that pre-service teachers who received the EE course had higher environmental knowledge and pro-environmental behaviour than their counterparts who did not take the EE course. Moreover, pre-service teachers who did not take the EE course had higher pro-environmental beliefs than their counterparts who received the EE course. However, the recorded mean differences were minor and not statistically significant. Also, the relationships between environmental knowledge, pro-environmental beliefs and pro-environmental behaviours were not significant. The implications of these findings call for EE policies and practices anchored on promoting personal environmental norms and citizenship and updated capacity building for EE educators.